POLAND–UKRAINE RELATIONS IN THE DIGITAL POLITICAL DISCOURSE OF POLAND (ON THE MATERIAL OF POLISH PRESIDENT OFFICIAL WEBSITE IN 2004-2015) - Steblyna, N. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
In this study news policy of the polish president official website is regarded to be a mirror of Poland – Ukraine relations. It’s assumed that it’s possible to recreate the dynamics of international relations forming within both news geography analysis (comparative analysis of different countries coverage) and formal analysis of news headlines types. News from news archive of the official website of the President of the Republic of Poland were collected and content-analyzed for the dynamics of international relations recreation. With the simple qualitative comparable analysis was shown, that Ukraine was the most popular country among the post-Soviet countries (it was so even before the Euromaidan). And the change of Ukraine presidents in 2010 with radical shift of international orientations didn’t reflect the intensity of attention. With the additional analysis of headlines types was shown, that for Poland Ukraine isn’t only the most popular country, the contacts with it are more varied than mutual relations with other countries. It can be demonstrated with the different levels and different formats usage. In the result of comparison with Polish – Russia relations was demonstrated, that the similar approach towards seeking ways for maintain relations between the countries was used (especially before 2008), however, it was con the deficit of both attention intensity and headlines variety. In the cases of Georgia and Ukraine news policy is more formal for Georgia, more detailed and informal for Ukraine. Thus, comparative analysis of different types of headlines use shows a special, attentive and favorable attitude towards Ukraine, which don’t change during Ukrainian changes of priorities in international politics and during times of crises. During the latter, Poland implements more new formats of contacts with Ukrainian politicians and appeals for wide network of international community. Meanwhile, the analysis have some limitations. It may be implemented only for countries with high number of mentions and doesn’t consider the types of news and. Thus, it’s may be complicated to define the essence of international relations. So, there is a need to define other formal approaches, which will help to classify texts.